2012
DOI: 10.1002/eji.201142173
|View full text |Cite
|
Sign up to set email alerts
|

M‐CSF induces the expression of a membrane‐bound form of IL‐18 in a subset of human monocytes differentiating in vitro toward macrophages

Abstract: IL-18 is a proinflammatory cytokine belonging to the "IL-1 family" that has been shown to play a prominent role in the induction of type 1 immune responses. Here, we show that M-CSF induces the expression of a membrane-bound form of IL-18 (mIL-18) in a subset of human blood monocytes differentiating toward macrophages. While monocytes, DC, and GM-CSF-treated monocytes did not express mIL-18, its expression was detected in ap- IntroductionMacrophages produce IL-1 (IL-1α and IL-1β) and IL-18, proinflammatory cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
87
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 42 publications
2
87
0
Order By: Relevance
“…1). In line with previous data [14,18], mIL-18 showed a bimodal distribution and was detected in a subset (30-40%) of in vitro-derived M2 cells. IIIc PT2 71 IIIc PT3 76 IIIc PT4 83 IIIc PT5 41 IIIc PT6 77 IIIc PT7 60 IIIc PT8 57 IIIc PT9 75 IIIc PT10 44 IIIc PT11 67 IV PT12 72 IIIc PT13 67 IIIc PT14 59 IV PT15 86 IIIc PT16 77 IIIc On the other hand, mIL-18 was expressed by most ex vivo-purified TAMs and its surface density was significantly higher than in M2 cells (Fig.…”
supporting
confidence: 92%
See 1 more Smart Citation
“…1). In line with previous data [14,18], mIL-18 showed a bimodal distribution and was detected in a subset (30-40%) of in vitro-derived M2 cells. IIIc PT2 71 IIIc PT3 76 IIIc PT4 83 IIIc PT5 41 IIIc PT6 77 IIIc PT7 60 IIIc PT8 57 IIIc PT9 75 IIIc PT10 44 IIIc PT11 67 IV PT12 72 IIIc PT13 67 IIIc PT14 59 IV PT15 86 IIIc PT16 77 IIIc On the other hand, mIL-18 was expressed by most ex vivo-purified TAMs and its surface density was significantly higher than in M2 cells (Fig.…”
supporting
confidence: 92%
“…Notably, a subset (30-40%) of M2 cells expressed a membrane-bound form of IL-18 (mIL-18) that was released upon TLR stimulation. This soluble form of IL-18 (sIL-18), by acting in close cell-to-cell contact, was crucial for both IFN-γ release and expression of CCR7 by NK cells [18]. Here, we analyzed the surface phenotype and functional properties of NK cells and TAMs from ovarian cancer patients as well as the functional outcome of the interaction between TAMs and freshly isolated NK cells.…”
Section: Introductionmentioning
confidence: 99%
“…IL-18 potentiates the immune response against viruses but has also been linked to the pathogenesis of atherosclerosis, active psoriasis, systemic lupus erythematosus, rheumatoid arthritis, Crohn's disease, and graftversus-host disease [44]. It has recently been reported that besides the soluble form, IL-18 is expressed as a membrane-bound protein in human blood CD16 − and CD16 + monocytes differentiating to macrophages by M-CSF stimulation [45].Human macrophages were chosen as a cell model for this study since they produce IL-18 and express several P2 receptor subtypes, particularly P2X7 that has been previously shown to trigger MVs release from other cell types [2,24]. Here we show that stimulation of human macrophages with the pan P2 agonist ATP or the P2X7 agonist BzATP induced shedding of MVs within minutes.…”
mentioning
confidence: 99%
“…The p16 fragmentinduced IFN-γ production in vitro but with only approximately 20% of the activity of mature IL-18 (26). Adding supernatant from human CD8 + T cells containing granzyme B (GrB) resulted in cleavage at the same site as caspase-1 and resulted in active IL-18 (27 (30,31). PR3 could also be the mechanism by which pro-IL-1β and pro-IL-18 released from a dying cell are activated.…”
Section: Interleukin-18 An Il-1 Family Membermentioning
confidence: 99%